Minimizing the maintenance costs of shuttle bus services using iterative heuristic - Mat Desa, Wan Laailatul Hanim; Alwi, Azatuliffah; Gan, Sheue Lynn; Soo, Jing Wen (2018)
Spending on maintenance and repair services is a normal activity faced by shuttle bus management. Without well planned on managing maintenance and repair cost may contribute to shorten life span of vehicles due to breakdowns.However, proper management of maintenance and repair services would keep the vehicle in good condition and longer service life.In this study, a formulation of mathematical modelling is proposed based on iterative local search by using Heuristic Techniques.The objective function is to minimize the maintenance cost while assigning only one cell to each repair agencies.The collected data has been computed into assignment problem, and solved using an iterative local search of the improved algorithms.This study will be helpful to improve the management system of UNIbus in terms of costs savings.The formulation will be repeated for at least 3 iteration sets, as the stated objective function.Empirical results show the optimal solution as expected.A few suggestions have been made based on the experimental results for identifying the best solution to optimize objective function.